Effect of microwave-assisted hydrothermal extraction on the bioactive compounds and antioxidant activities of dateplum persimmon juice and vinegar. (15th January 2022) - Hu, Yue; Yan, Huanhuan; Yin, Yuxi; Li, Xue; Li, Hairong; Ren, Di Feng
Abstract: In this study, it was aimed to determine the effect of microwave-assisted hydrothermal extraction (MHE) on the bioactive compounds, phenolic profile, and antioxidant activities of dateplum persimmon ( Diospyros lotus L) juice and vinegar, compared to those prepared by microwave (ME) and hydrothermal (HE) extraction. Results showed that following optimization by response surface methodology, the total phenolic content of dateplum persimmon juice reached 166.8 ± 2.2 mg/g at 131 °C, 26 mL/g, 390 W, and 32 min. The microstructural morphological changes to dateplum persimmon juice and their bioactive compound contents were ranked in the order of MHE-, HE-, and ME-prepared, and untreated juice from highest to lowest. Both MHE-prepared juice and vinegar presented high polyphenol, protein, and polysaccharide contents. Pyrogallol, gallic acid, protocatechuic acid, quercetin-3β-D-glucoside, ellagic acid, quercetin, maslinic acid, and ursolic acid were identified in juice and vinegar. Compared to untreated dateplum persimmon juice and vinegar, the IC50 values for the DPPH, ABTS +, and OH scavenging activities were decreased by 71.4% and 70.8%, 72.4% and 70.7%, and 50.2% and 48.3% for juice and vinegar prepared by MHE, respectively. These findings suggest that MHE can be used as a novel technology for preparing phenolic-rich and high-antioxidant activity juice and vinegar. Highlights: MHE was optimized for preparing phenolic-rich dateplum persimmon juice. MHE enhanced polyphenol, protein, and polysaccharide contents of dateplum persimmon juice and vinegar. Protocatechuic acid was the most increased polyphenol by MHE. MHE improved the antioxidant activities of juice and vinegar by 2-fold.